Research on rural entrepreneurship in terms of the literature: Definition problems and selected research issues - Kulawiak, Anita; Suliborski, Andrzej; Rachwał, Tomasz (Quaestiones Geographicae, 2022)
Rural entrepreneurship has become an important research issue with great development potential in the face of intense socio-economic changes in rural areas. However, few significant studies cover this topic in Polish and foreign literature. In this article, the authors attempt to review and evaluate the current research on rural entrepreneurship emphasising the Polish literature and including geographical studies. The article describes and organises theoretical research achievements to date and offers a definition of rural entrepreneurship and the directions and prospects for further research.